A randomised controlled study of the post-operative analgesic efficacy of ultrasound-guided pectoral nerve block in the first 24 h after modified radical mastectomy - Kumar, Satish (Indian J Anaesth, 2018)
BACKGROUND AND AIMS: Breast cancer has become the most common cancer in women worldwide. Acute post-operative pain following mastectomy remains a challenge for the anaesthesiologist despite a range of treatment options available. The present study aimed to compare the post-operative analgesic efficacy of pectoral nerve (Pecs) block performed under ultrasound with our standard practice of opioids and non-steroidal anti-inflammatory drugs for mastectomy. METHODS: This randomised controlled study was conducted at a tertiary care teaching hospital in India, after obtaining ethical clearance. Fifty adult female patients posted for elective unilateral modified radical mastectomy were divided into two groups as follows: Group I (general anaesthesia only) and Group II (general anaesthesia plus ultrasound-guided Pecs block), each comprising 25 patients. Post-randomisation, patients in Group I received general anaesthesia, while Group II patients received ultrasound-guided Pecs block followed by general anaesthesia after 20 min. The primary outcome was measured as patient-reported pain intensity using Visual Analogue Scale (VAS) at rest. Statistical analysis was performed using Student's t-test and Mann–Whitney U-test. Data were entered into MS Excel spreadsheet and analysis was performed using the Statistical Package for the Social Sciences version 23.0. RESULTS: VAS score was significantly lower in Group II at rest and on abduction post-operatively at all time intervals (P < 0.001). The 24-h tramadol consumption was significantly less in Group II compared to Group I (114.4 ± 4.63 mg vs. 402.88 ± 74.22, P < 0.0001). CONCLUSION: Pecs block provided excellent post-operative analgesia in the first 24 h.